Effect of Lactobacillus Plantarum Fermentation Duration on the Physicochemical Properties of Chicken- Head Gelatin - Syafitri, Yosi; Lianti, Lita; Al Fajri, Adelia Khoirunnisa (Jurnal Pangan dan Agroindustri, 2026)
Chicken meat is widely consumed, whereas its by-products, such as chicken heads, remain underutilized. Chicken heads contain substantial amounts of collagen and therefore have potential as a raw material for gelatin production. This study evaluated Lactobacillus plantarum fermentation as a pretreatment for producing gelatin from chicken heads and determined the effect of fermentation duration on physicochemical properties. A completely randomized design was used with three fermentation durations: 24, 48, and 72 h. Fermentation duration significantly affected yield, moisture content, ash content, pH, viscosity, gel strength, and melting point, but did not significantly affect gelation temperature.